2021
DOI: 10.1186/s12888-021-03271-6
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the association between religious coping, fatigue, anxiety and depressive symptoms during the COVID-19 pandemic in Morocco: a web-based cross-sectional survey

Abstract: Background The Coronavirus Disease 2019 (COVID-19) pandemic has triggered fear and distress among the public, thus potentiating the incidence rate of anxiety and depression. This study aims to investigate the psychological effect of quarantine on persons living in Morocco when the first COVID-19 cases were identified. The associations between anxiety, depression symptoms, and their predictors (sociodemographics, fatigue, and religious coping) were examined. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 62 publications
1
25
0
3
Order By: Relevance
“… Iddi et al (2021) also revealed that individuals who were concerned about their safety amidst COVID-19 coped very well. Other studies have also shown that religious coping was associated with COVID-19 related anxiety ( Chow et al, 2021 ; Yıldırım et al, 2021 ; Zarrouq et al, 2021 ). From the psychological resilience theory perspective, individuals can successfully cope with events perceived as stressful and preserve their psychological function even in adversity, because internal and external protective strategies can help ease the negative impact of these challenging events ( Main et al, 2011 ; Luthar et al, 2015 ; Lyons et al, 2016 ).…”
Section: Introductionmentioning
confidence: 84%
“… Iddi et al (2021) also revealed that individuals who were concerned about their safety amidst COVID-19 coped very well. Other studies have also shown that religious coping was associated with COVID-19 related anxiety ( Chow et al, 2021 ; Yıldırım et al, 2021 ; Zarrouq et al, 2021 ). From the psychological resilience theory perspective, individuals can successfully cope with events perceived as stressful and preserve their psychological function even in adversity, because internal and external protective strategies can help ease the negative impact of these challenging events ( Main et al, 2011 ; Luthar et al, 2015 ; Lyons et al, 2016 ).…”
Section: Introductionmentioning
confidence: 84%
“…Adolescents are still progressing a perspective of the world and do not yet possess a satisfactory answer on the meaning of life (Giannone & Kaplin, 2020). They also own the frequency of accessing news of the COVID-19 pandemic through social media, which makes them more vulnerable to anxiety and depression (Zarrouq et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Research in the United Arab Emirates (UAE) confirmed this relationship by comparing spirituality between Christians and Muslims (Thomas, & Barbato, 2020). Many other studies have also evident the relationship between spirituality and depression (Davis et al, 2021), (Zarrouq et al, 2021), (Askari et al, 2018).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations